Pemanfaatan Buah Mangga Dengan Sistem Informasi Pengolahan Pasteurisasi - Hasyim, M.Ardi Nupi; Lisnawati, Tina; Maulaniewati, Siti Ulfah; Kurniawan, Jajang (Jurnal Riset Manajemen Indonesia, 2023)
Mango production in West Java during 2008-2013 ranks third with a total production of 16.52% of the total national mango production. Mango-producing areas in West Java are spread in 27 districts and cities. Mango-producing centers in West Java are in the districts of Cirebon, Majalengka, and Indramayu with varieties of Gedong Gincu, Dermayu, Kidang, and Arumanis. Until now, farmers still have difficulty in accessing the market, so that during harvest time, there are always unsold or discarded mangoes. Off Grade mangoes even at harvest can reach 30% of total production, of course this can be detrimental to farmers. In 2005 a study was conducted by Dwi Purnomo. Off grade mangoes are processed into a puree (fruit porridge) which is processed through pasteurization technology or the cooking process by heating them at a temperature of 70 to 80 degrees. The process used here is the benefit chain method that is from upstream to downstream how the utilization process involves rural communities to the city, not apart from that one of the students who helped the research also helped with the marketing process.